From green waste to horticultural resources: A novel approach to quantifying greenhouse gas emission factors for decision-making - Takanori Kuronuma; Hitoshi Watanabe; Azusa Gomi; Shohei Masuda; Takuya Mito (Journal of Environmental Management, 2026)

The genetic population structure and diversity of the endangered bittering Pseudorhodeus tanago revealed by SNP markers - Yoshimitsu Takada; Takahiro Morosawa; Masaki Asano; Ryoichi Tabata; Hitoshi Kubota; Katsutoshi Watanabe (Ichthyological Research, 2026)

Three Kampo medicines—bofutsushosan, boiogito, and daisaikoto—have different effects on host fat accumulation and the intestinal microbiota in a high-fat-diet–induced mouse model of obesity - Kosuke Nakamichi; Tetsuhiro Yoshino; Masahiro Akiyama; Aya Jibiki; Yuta Yokoyama; Hitoshi Kawazoe; Sayo Suzuki; Kenji Watanabe; Yun-Gi Kim; Tomonori Nakamura (Journal of Natural Medicines, 2025)
Inhibiting body fat accumulation is important for the prevention of obesity. In Japan, three Kampo medicines are commonly used to treat obesity: bofutsushosan, boiogito, and daisaikoto. To compare the influences of these Kampo medicines on the intestinal microbiota, it is necessary to conduct a simultaneous investigation using the same mouse model under the same experimental conditions. C57BL/6J mice were divided into five groups: normal chow (NC), high-fat diet (HFD), HFD + 3% bofutsushosan extract (BTS), HFD + 3% boiogito extract (BOT), and HFD + 3% daisaikoto extract (DST). Epididymal white adipose tissue (WAT) weight, mesenteric WAT weight, serum triglyceride levels, and serum total cholesterol levels were measured. Additionally, total bacteria, alpha diversity, beta diversity, and bacterial composition in stool samples were measured. Body weight and epididymal WAT weight gain were significantly inhibited in the BTS-treated group and DST-treated group, but not in the BOT-treated group, compared with the HFD control group. Additionally, serum total cholesterol levels were significantly lower in the DST-treated group than in the HFD group. Specific intestinal bacteria, Clostridium sensu stricto 1 , Erysipelatoclostridium , Roseburia , and the Lachnospiraceae NK4A136 group, were significantly changed in the Kampo-treated groups compared with the HFD group, and each of them was correlated with body weight gain, body fat rate, epididymal WAT weight, or mesenteric WAT weight. Our simultaneous investigation of BTS, BOT, and DST under the same conditions clearly demonstrated different changes in the intestinal microbiota and different effects on fat accumulation as well as their association among the three Kampo medicines. Graphical abstract

Investigating real-time thermal sensation predictions using predicted mean vote and local skin temperature analysis via infrared thermography as a nonintrusive tool - Biplob Kanti Biswas; Koichi Ishii; Kaisei Okamoto; Yu Watanabe; Jiating Li; Yumiko Tan; Ayano Dempoya; Sang-il Lee; Takuji Iwamura; Shingo Konoshita; Hitoshi Wakabayashi (Energy and Buildings, 2025)

Ten new resin glycosides, ipoalbins I–X, from Ipomoea alba seeds - Nodoka Misuda; Mizuki Watanabe; Hirotaka Nishikawa; Shin Yasuda; Hiroyuki Miyashita; Kazumi Yokomizo; Hitoshi Yoshimitsu; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo; Masateru Ono (Journal of Natural Medicines, 2025)

Predicting individual variability in thermal sensation, PMV predictions, and local skin temperature differences using infrared thermography - Biplob Kanti Biswas; Koichi Ishii; Yu Watanabe; Jiating Li; Yumiko Tan; Ayano Dempoya; Sang-il Lee; Takuji Iwamura; Shingo Konoshita; Hitoshi Wakabayashi (Building and Environment, 2025)

Disruption in Jasmonic Acid Biosynthesis Influences Metabolism of Other Hormones in Arabidopsis - Aarti Gupta; Yasuko Watanabe; Chien Van Ha; Mostafa Abdelrahman; Weiqiang Li; Md. Mezanur Rahman; Sanjida Sultana Keya; Deepti Nigam; Yinping Jiao; Touhidur Rahman Anik; Gopal Saha; Mikiko Kojima; et al. (Journal of Plant Growth Regulation, 2025)

Improved GAN-based deep learning approach for strain field prediction and failure analysis of precast bridge slab joints - Qiliang Zhao; Bochao Sun; Weijian Zhao; Takahiko Watanabe; Tatsuya Usui; Hitoshi Takeda (Engineering Structures, 2024)

Inclusive greenhouse gas budget assessment in turfs: From turf production to disposal of grass clippings - Takanori Kuronuma; Shohei Masuda; Takuya Mito; Hitoshi Watanabe (Journal of Environmental Management, 2023)

Methoxyflavones isolated from the whole plant of Scutellaria rubropunctata Hayata var. rubropunctata promote osteoblast differentiation in MC3T3-E1 cells - Misaki Watanabe; Tadahiro Yahagi; Rina Kamikura; Hitoshi Kotani; Katsunori Miyake; Keiichi Matsuzaki (Journal of Natural Medicines, 2023)

Novel extracellular role of REIC/Dkk-3 protein in PD-L1 regulation in cancer cells - Yuma Gohara; Nahoko Tomonobu; Rie Kinoshita; Junichiro Futami; Léna Audebert; Youyi Chen; Ni Luh Gede Yoni Komalasari; Fan Jiang; Chikako Yoshizawa; Hitoshi Murata; Ken-ichi Yamamoto; Masami Watanabe; et al. (Journal of Molecular Medicine, 2023)
The adenovirus-REIC/Dkk-3 expression vector (Ad-REIC) has been the focus of numerous clinical studies due to its potential for the quenching of cancers. The cancer-suppressing mechanisms of the REIC/DKK- 3 gene depend on multiple pathways that exert both direct and indirect effects on cancers. The direct effect is triggered by REIC/Dkk-3-mediated ER stress that causes cancer-selective apoptosis, and the indirect effect can be classified in two ways: (i) induction, by Ad-REIC-mis-infected cancer-associated fibroblasts, of the production of IL-7, an important activator of T cells and NK cells, and (ii) promotion, by the secretory REIC/Dkk-3 protein, of dendritic cell polarization from monocytes. These unique features allow Ad-REIC to exert effective and selective cancer-preventative effects in the manner of an anticancer vaccine. However, the question of how the REIC/Dkk-3 protein leverages anticancer immunity has remained to be answered. We herein report a novel function of the extracellular REIC/Dkk-3—namely, regulation of an immune checkpoint via modulation of PD-L1 on the cancer-cell surface. First, we identified novel interactions of REIC/Dkk-3 with the membrane proteins C5aR, CXCR2, CXCR6, and CMTM6. These proteins all functioned to stabilize PD-L1 on the cell surface. Due to the dominant expression of CMTM6 among the proteins in cancer cells, we next focused on CMTM6 and observed that REIC/Dkk-3 competed with CMTM6 for PD-L1, thereby liberating PD-L1 from its complexation with CMTM6. The released PD-L1 immediately underwent endocytosis-mediated degradation. These results will enhance our understanding of not only the physiological nature of the extracellular REIC/Dkk-3 protein but also the Ad-REIC-mediated anticancer effects. Key messages • REIC/Dkk-3 protein effectively suppresses breast cancer progression through an acceleration of PD-L1 degradation. • PD-L1 stability on the cancer cell membrane is kept high by binding with mainly CMTM6. • Competitive binding of REIC/Dkk-3 protein with CMTM6 liberates PD-L1, leading to PD-L1 degradation.

Development of an oral mucosal irritation test using a three-dimensional human buccal oral mucosal model - Seiya Aizawa; Hidenori Yoshida; Kazuhiko Umeshita; Shinichi Watanabe; Yutaka Takahashi; Shinji Sakane; Hitoshi Sakaguchi; Shinsuke Kataoka (Toxicology in Vitro, 2023)

A longitudinal study of Candida bloodstream infections in a Japanese university hospital: species distribution, drug susceptibility, clinical features, and mortality predictors - Hitoshi Tsukamoto; Takashi Higashi; Takaaki Kodawara; Kyohei Watanabe; Yukio Hida; Hiromichi Iwasaki; Nobuyuki Goto (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Fundamental Study on Water Stress Detection in Sugarcane Using Thermal Image Combined with Photosynthesis Measurement Under a Greenhouse Condition - Kenta Watanabe; Hitoshi Agarie; Kittipon Aparatana; Muneshi Mitsuoka; Eizo Taira; Masami Ueno; Yoshinobu Kawamitsu (Sugar Tech, 2022)

Correction to: Physiologically based pharmacokinetic modelling to predict the clinical effect of CYP3A inhibitors/inducers on esaxerenone pharmacokinetics in healthy subjects and subjects with hepatic impairment - Akiko Watanabe; Tomoko Ishizuka; Makiko Yamada; Yoshiyuki Igawa; Takako Shimizu; Hitoshi Ishizuka (European Journal of Clinical Pharmacology, 2022)

Physiologically based pharmacokinetic modelling to predict the clinical effect of CYP3A inhibitors/inducers on esaxerenone pharmacokinetics in healthy subjects and subjects with hepatic impairment - Akiko Watanabe; Tomoko Ishizuka; Makiko Yamada; Yoshiyuki Igawa; Takako Shimizu; Hitoshi Ishizuka (European Journal of Clinical Pharmacology, 2022)
Purpose Esaxerenone is a novel, oral, nonsteroidal treatment for hypertension. Physiologically based pharmacokinetic (PBPK) modelling was performed to predict the drug–drug interaction (DDI) effect of cytochrome P450 (CYP)3A modulators on esaxerenone pharmacokinetics in healthy subjects and subjects with hepatic impairment. Methods In our PBPK model, the fraction of esaxerenone metabolised by CYP3A was estimated from mass-balance data and verified and optimised by clinical DDI study results with strong CYP3A modulators. The model was also verified by the observed pharmacokinetics after multiple oral dosing and by the effect of hepatic impairment on esaxerenone pharmacokinetics. The model was applied to predict the DDI effects on esaxerenone pharmacokinetics with untested CYP3A modulators in healthy subjects and with strong CYP3A modulators in subjects with hepatic impairment. Results The PBPK model well described esaxerenone pharmacokinetics after multiple oral dosing. The predicted fold changes in esaxerenone plasma exposure after coadministration with strong CYP3A modulators were comparable with the observed data (1.53-fold with itraconazole and 0.31-fold with rifampicin). Predicted DDIs with untested moderate CYP3A modulators were less than the observed DDI with strong CYP3A modulators. The PBPK model also described the effect of hepatic impairment on esaxerenone plasma exposure. The predicted DDI results with strong CYP3A modulators in subjects with hepatic impairment indicate that, for concomitant use of CYP3A modulators, caution is advised for subjects with hepatic impairment, as is for healthy subjects. Conclusion The PBPK model developed predicted esaxerenone pharmacokinetics and DDIs and informed concurrent use of esaxerenone with CYP3A modulators.

MCAM, as a novel receptor for S100A8/A9, mediates progression of malignant melanoma through prominent activation of NF-κB and ROS formation upon ligand binding - I. Made Winarsa Ruma; Endy Widya Putranto; Eisaku Kondo; Hitoshi Murata; Masami Watanabe; Peng Huang; Rie Kinoshita; Junichiro Futami; Yusuke Inoue; Akira Yamauchi; I. Wayan Sumardika; Chen Youyi; et al. (Clinical & Experimental Metastasis, 2016)

Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Is Involved in Adult Mouse Hippocampal Neurogenesis After Stroke - Minako Matsumoto; Tomoya Nakamachi; Jun Watanabe; Koichi Sugiyama; Hirokazu Ohtaki; Norimitsu Murai; Shun Sasaki; Zhifang Xu; Hitoshi Hashimoto; Tamotsu Seki; Akira Miyazaki; Seiji Shioda (Journal of Molecular Neuroscience, 2016)

Cyclophilin A is a new M cell marker of bovine intestinal epithelium - Tetsuya Hondo; Shunsuke Someya; Yuya Nagasawa; Shunsuke Terada; Hitoshi Watanabe; Xiangning Chen; Kouichi Watanabe; Shyuichi Ohwada; Haruki Kitazawa; Michael T. Rose; Tomonori Nochi; Hisashi Aso (Cell and Tissue Research, 2016)

Genome-wide association study identifies a PSMD3 variant associated with neutropenia in interferon-based therapy for chronic hepatitis C - Etsuko Iio; Kentaro Matsuura; Nao Nishida; Shinya Maekawa; Nobuyuki Enomoto; Mina Nakagawa; Naoya Sakamoto; Hiroshi Yatsuhashi; Masayuki Kurosaki; Namiki Izumi; Yoichi Hiasa; Naohiko Masaki; et al. (Human Genetics, 2015)

Expression of Myostatin in Neural Cells of the Olfactory System - Shunsuke Iwasaki; Masato Miyake; Hitoshi Watanabe; Eri Kitagawa; Kouichi Watanabe; Shyuichi Ohwada; Haruki Kitazawa; Michael T. Rose; Hisashi Aso (Molecular Neurobiology, 2013)

Association of Verticillium dahliae and Verticillium longisporum with Chinese cabbage yellows and their distribution in the main production areas of Japan - Kentaro Ikeda; Shinpei Banno; Ken Watanabe; Masashi Fujinaga; Hideki Ogiso; Hiroshi Sakai; Hitoshi Tanaka; Shizue Miki; Satoshi Shibata; Toshimasa Shiraishi; Makoto Fujimura (Journal of General Plant Pathology, 2012)

AMPK activation by AICAR inhibits myogenic differentiation and myostatin expression in Cattle - Masato Miyake; Hideyuki Takahashi; Eri Kitagawa; Hitoshi Watanabe; Takahiro Sakurada; Hisashi Aso; Takahiro Yamaguchi (Cell and Tissue Research, 2012)

Concerns about inherited risk of breast cancer prior to diagnosis in Japanese patients with breast complaints - Noriko Ando; Yumi Iwamitsu; Masaru Kuranami; Shigemi Okazaki; Kenji Yamamoto; Masahiko Watanabe; Hitoshi Miyaoka (Familial Cancer, 2011)

Effects of soil pH on rhizoctonia damping-off of sugar beet and disease suppression induced by soil amendment with crop residues - Kaori Watanabe; Mariko Matsui; Hitoshi Honjo; J. Ole Becker; Ryo Fukui (Plant and Soil, 2011)

Nucleotide sequence and chromosomal localization of the gene for pierisin-1, a DNA ADP-ribosylating protein, in the cabbage butterfly Pieris rapae - Masafumi Yamamoto; Azusa Takahashi-Nakaguchi; Yuko Matsushima-Hibiya; Tsuyoshi Nakano; Yukari Totsuka; Shigeo Imanishi; Jun Mitsuhashi; Masahiko Watanabe; Hitoshi Nakagama; Takashi Sugimura; Keiji Wakabayashi (Genetica, 2011)

Enhanced expression of fibroblast growth factor 2 in bone marrow cells and its potential role in the differentiation of hepatic epithelial stem-like cells into the hepatocyte lineage - Hiroaki Haga; Takafumi Saito; Kazuo Okumoto; Satoshi Ugajin; Chikako Sato; Rika Ishii; Yuko Nishise; Junitsu Ito; Hisayoshi Watanabe; Koji Saito; Hitoshi Togashi; Sumio Kawata (Cell and Tissue Research, 2011)

Genetic population structure and management units of the endangered Tokyo bitterling, Tanakia tanago (Cyprinidae) - Hitoshi Kubota; Katsutoshi Watanabe; Naoyuki Suguro; Masaaki Tabe; Kazuhiro Umezawa; Seiichi Watanabe (Conservation Genetics, 2010)

Dominant-negative mutant hepatocyte nuclear factor 1α induces diabetes in transgenic-cloned pigs - Kazuhiro Umeyama; Masahito Watanabe; Hitoshi Saito; Mayuko Kurome; Sadaaki Tohi; Hitomi Matsunari; Keizaburo Miki; Hiroshi Nagashima (Transgenic Research, 2009)

A small heat-shock protein confers stress tolerance and stabilizes thylakoid membrane proteins in cyanobacteria under oxidative stress - Kollimalai Sakthivel; Tatsuro Watanabe; Hitoshi Nakamoto (Archives of Microbiology, 2009)

Green corolla segments in a wild Petunia species caused by a mutation in FBP2, a SEPALLATA-like MADS box gene - Kiyoshi Matsubara; Katsuyoshi Shimamura; Hiroaki Kodama; Hisashi Kokubun; Hitoshi Watanabe; Isabel L. Basualdo; Toshio Ando (Planta, 2008)

An assessment of genetic diversity in wild and captive populations of endangered Japanese bitterling Tanakia tanago (Cyprinidae) using amplified fragment length polymorphism (AFLP) markers - Hitoshi KUBOTA; Katsutoshi WATANABE; Yoko KAKEHI; Seiichi WATANABE (Fisheries Science, 2008)

Constitutive Overexpression of P-glycoprotein, Rather than Breast Cancer Resistance Protein or Organic Cation Transporter 1, Contributes to Acquisition of Imatinib-Resistance in K562 Cells - Chie Hirayama; Hiroshi Watanabe; Reiko Nakashima; Takeru Nanbu; Akinobu Hamada; Akihiko Kuniyasu; Hitoshi Nakayama; Tatsuya Kawaguchi; Hideyuki Saito (Pharmaceutical Research, 2008)

Phylogenetic analysis of the genus Petunia (Solanaceae) based on the sequence of the Hf1 gene - Sumei Chen; Kiyoshi Matsubara; Takahiro Omori; Hisashi Kokubun; Hiroaki Kodama; Hitoshi Watanabe; Goro Hashimoto; Eduardo Marchesi; Laura Bullrich; Toshio Ando (Journal of Plant Research, 2007)

Genetic identification of native populations of fluvial white-spotted charr Salvelinus leucomaenis in the upper Tone River drainage - Hitoshi KUBOTA; Takahide DOI; Shoichiro YAMAMOTO; Seiichi WATANABE (Fisheries Science, 2007)

Mitochondrial haplogroup N9b is protective against myocardial infarction in Japanese males - Yutaka Nishigaki; Yoshiji Yamada; Noriyuki Fuku; Hitoshi Matsuo; Tomonori Segawa; Sachiro Watanabe; Kimihiko Kato; Kiyoshi Yokoi; Sachiyo Yamaguchi; Yoshinori Nozawa; Masashi Tanaka (Human Genetics, 2007)

Distribution of self-compatible and self-incompatible populations of Petunia axillaris (Solanaceae) outside Uruguay - Hisashi Kokubun; Makoto Nakano; Tatsuya Tsukamoto; Hitoshi Watanabe; Goro Hashimoto; Eduardo Marchesi; Laura Bullrich; Isabel L. Basualdo; Teh-hui Kao; Toshio Ando (Journal of Plant Research, 2006)

A SINE Family Widely Distributed in the Plant Kingdom and its Evolutionary History - Jeffrey A. Fawcett; Taihachi Kawahara; Hitoshi Watanabe; Yasuo Yasui (Plant Molecular Biology, 2006)

Molecular characterization of mature pollen-specific genes encoding novel small cysteine-rich proteins in rice (Oryza sativa L.) - Jong-In Park; Hirokazu Hakozaki; Makoto Endo; Yoshinobu Takada; Hitoshi Ito; Masanori Uchida; Tomihiro Okabe; Masao Watanabe (Plant Cell Reports, 2006)

Duplication of the S-locus F-box gene is associated with breakdown of pollen function in an S-haplotype identified in a natural population of self-incompatible Petunia axillaris - Tatsuya Tsukamoto; Toshio Ando; Hitoshi Watanabe; Eduardo Marchesi; Teh-hui Kao (Plant Molecular Biology, 2005)

Effects of angiotensin-II receptor blocker candesartan cilexetil in rats with dilated cardiomyopathy - Ken Shirai; Kenichi Watanabe; Meilei Ma; Mir I I Wahed; Mikio Inoue; Yuki Saito; Palaniyandi Selvaraj Suresh; Takeshi Kashimura; Hitoshi Tachikawa; Makoto Kodama; Yoshifusa Aizawa (Molecular and Cellular Biochemistry, 2005)

Binding site of novel 2-benzylamino-4-methyl-6-trifluoromethyl-1,3,5- triazine herbicides in the D1 protein of Photosystem II - Yumi Ikeda; Shinpei Ohki; Kazuya Koizumi; Akira Tanaka; Hiroyuki Watanabe; Hitoshi Kohno; Jack J. S. van Rensen; Peter Böger; Ko Wakabayashi (Photosynthesis Research, 2003)

Oxidation of sarcoplasmic reticulum Ca2+-ATPase induced by high-intensity exercise - Satoshi Matsunaga; Shuichiro Inashima; Takashi Yamada; Hitoshi Watanabe; Toshio Hazama; Masanobu Wada (Pflügers Archiv - European Journal of Physiology, 2003)

Genetic diversity in wild and reared populations of the Japanese bitterling Tanakia tanago (Cyprinidae) - Hitoshi Kubota; Katsutoshi Watanabe (Ichthyological Research, 2003)

Activity and population structure of nitrifying bacteria in an activated‐sludge reactor containing polymer beads - Jun‐ichi Tanaka; Kazuaki Syutsubo; Kazuya Watanabe; Hitoshi Izumida; Shigeaki Harayama (Environmental Microbiology, 2003)
Summary Photo‐crosslinked polymer beads were introduced into a laboratory activated‐sludge unit containing municipal sewage sludge and the effect on nitrifying capacity was examined. The ammonia load started at a nitrogen‐loading rate of 0.02 kg m −3 day −1 and was increased stepwise. It was found that the bead‐containing unit could almost completely oxidize ammonia (over 95%) up to a nitrogen‐loading rate of 0.216 kg m −3 day −1 , whereas the maximum loading rate of the control unit (without polymer beads) was 0.096 kg m −3 day −1 . The nitrifying potential of suspended and bead‐associated organisms in the bead‐containing unit was measured under different loading conditions. It was found that the bead‐associated organisms exhibited high specific activities under high loading conditions and that the contribution of the bead‐associated organisms to nitrification was greater than that of the suspended solids under these conditions. The bacterial population dynamics in the suspended solids and bead‐associated organisms were analysed by denaturing gradient gel electrophoresis (DGGE) of PCR‐amplified 16S rRNA gene fragments and by fluorescence in situ hybridization with group‐specific probes. Among the known nitrifying organisms, ammonia‐oxidizing β‐proteobacteria and Nitrospira ‐related organisms were detected by these approaches. A comparison of the activity dynamics and population dynamics, however, suggested a possibility that other organisms may also have been involved in the nitrification process under high loading conditions.

Use of ovule culture to cross between Delphinium species of different ploidy - Kazushige Honda; Hitoshi Watanabe; Kiyoshi Tsutsui (Euphytica, 2003)

Cryopreservation of Delphinium pollen at –30 °C - Kazushige Honda; Hitoshi Watanabe; Kiyoshi Tsutsui (Euphytica, 2002)

Enhancement of N-methyl-D-aspartate receptor-mediated excitatory postsynaptic potentials in the neostriatum after methamphetamine sensitization - Shigeki Moriguchi; Shigenori Watanabe; Hitoshi Kita; Hiroshi Nakanishi (Experimental Brain Research, 2002)

Diversity of Hepatitis G Virus within a Single Infected Individual - Li Shao; Haruhide Shinzawa; Xuhong Zhang; Donald B. Smith; Hisayoshi Watanabe; Hideki Mitsuhashi; Koji Saito; Takafumi Saito; Hitoshi Togashi; Tsuneo Takahashi (Virus Genes, 2000)

Evaluation of Cytotoxicity of Various Ophthalmic Drugs, Eye Drop Excipients and Cyclodextrins in an Immortalized Human Corneal Epithelial Cell Line - Paula Saarinen-Savolainen; Tomi Järvinen; Kaoru Araki-Sasaki; Hitoshi Watanabe; Arto Urtti (Pharmaceutical Research, 1998)